18.1k views
2 votes
1.06g - 3 = 0.71 I need this answer

2 Answers

0 votes
1.06g -3=0.71 1.06g =0.71+3 1.06g=0.74 both side by 1.06 g =0.74/1.06
User Gjon
by
5.6k points
5 votes
Simplifying 1.06g + -3 = 0.71 Reorder the terms: -3 + 1.06g = 0.71 Solving -3 + 1.06g = 0.71 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 1.06g = 0.71 + 3 Combine like terms: -3 + 3 = 0 0 + 1.06g = 0.71 + 3 1.06g = 0.71 + 3 Combine like terms: 0.71 + 3 = 3.71 1.06g = 3.71 Divide each side by '1.06'. g = 3.5 Simplifying g = 3.5
User Simon Miller
by
5.6k points